Nutritional Water Productivity and Global Food Security - Ali, Nawab (Journal of Agricultural Engineering, 2011)
Water is life and is one of the major inputs for agriculture. Earth has a finite supply of fresh water and therefore, demands that every drop of annual rainfall should be conserved and judiciously utilized for production and postproduction agriculture to get maximum nutrients per unit of water. The concept of water productivity in agriculture is now shifting from harvest index per unit of land and water to nutrients (protein, carbohydrate, fat, etc.) produced per unit of water. This varies with food commodities and locations. For example, the total dietary energy produced by potato, maize, peanut, wheat, milk, egg and beef using one m3of water are about 5600 kcal, 3800 kcal, 2300 kcal, 2280 kcal, 660 kcal, 520 kcal and 100 kcal, respectively. Similarly, the production of protein using one mÂ³ of water by potato, peanut, maize, wheat, egg, milk, chicken, and beef are 150 g, 111 g, 77 g, 74 g, 41 g, 40 g, 33 g and 10 g, respectively. This paper describes the water nutrient productivity of some of the crops and livestock products and suggests as to how to provide food and nutritional security through an appropriate and balanced diet design, to the maximum number of people of the world from the limited and dwindling land, water and bio resources.